(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
India is agriculture dominant country and organophosphorus commonly used by former in agriculture field. Therefore, Organophosphorus poisoning is common India. Study done at emergency department to know the pattern of sign and symptoms presentation at the time of admission. Total number of cases was 160, out of them 102 (64%) were males and only 58 (36%) were females. Male to female ratio was 1.75:1. farmers 61 (38%) were commonly affected, followed by 35(22%) of patients were housewives and 26 (16%) of patients were students. symptoms presented were vomiting 150 (93.75%) and salivation 150 (93.75%), followed by sweating 147 (91.88%), lacrimation 102 (63.75%) and blurring of vision 80 (50%), breathlessness (40%), faecal incontinence (31.88%), urinary incontinence (18.13%), headache (18.13%) and convulsion (10%). commonest signs were smell of poison 150 (93.75%), followed by tachypnoea 134 (83.75%), altered consciousness 115 (71.88%), miosis 86 (53.75%), fasciculation 70 (43.75%), tachycardia (36.25%), bradycardia (28.13) and pulmonary oedema (06.25%). Increased body secretions were the commonest presentation then other symptoms followed were blurring vision, tachypnoea altered consciousness, and respiratory symptoms. It can be helpful to make diagnosis and take awareness, preventive measures about organophosphorus poisoning.